A superelastochromic crystal - Toshiki Mutai (Nature Portfolio, 2020)
Color changes by external stimuli, so-called chromism, have been intensively studied to develop smart materials due to the stimulus-responsiveness of chromic materials. Here the authors demonstrate luminescent chromism during a mechanically controllable phase transition in a luminescent organosuperelastic crystal.